Sastra Anak Berbasis Studi Kebantenan sebagai Media Pembelajaran Bahasa Indonesia di Sekolah Dasar - Yoma Hatima; Rina Yuliana (FKIP UNSULTRA, 2026)
This study aims to examine the role of Bantenese-based children's literature as a medium for Indonesian language learning in elementary schools through a literature study approach. Children's literature that integrates local values, including Bantenese culture, has great potential in improving the quality of contextual, meaningful learning, and is oriented towards building students' character. The method used is a literature study by reviewing various scientific sources in the form of journals, books, and relevant research results published in the last ten years. The results of the study indicate that the use of Bantenese-based children's literature can improve students' language skills, especially in the aspects of reading, writing, listening, and speaking. In addition, this approach also strengthens local cultural identity and instills moral values ​​and character in students from an early age. Bantenese-based children's literature provides a more contextual learning experience because it links learning materials to students' daily lives. Other findings indicate that the use of local folktales, legends, and traditions in Indonesian language learning can increase students' learning motivation and develop their imagination and creativity. Thus, Bantenese-based children's literature can be used as an alternative, innovative and effective learning medium in improving the quality of Indonesian language learning in elementary schools. The implications of this research are the need to develop teaching materials based on local culture and to improve teacher competency in integrating children's literature into learning.